Decreased kidney function and agricultural work: a cross-sectional study in middle-aged adults from Tierra Blanca, Mexico. Issue 6 (22nd May 2020) - Aguilar-Ramirez, Diego; Raña-Custodio, Alejandro; Villa, Antonio; Rubilar, Ximena; Olvera, Nadia; Escobar, Alejandro; Johnson, Richard J; Sanchez-Lozada, Laura; Obrador, Gregorio T; Madero, Magdalena
Abstract: Background: We aimed to determine the prevalence of decreased kidney function in a potential chronic kidney disease (KD) of unknown aetiology hotspot in Mexico, assess its distribution across occupations and examine the associated risk factors. Methods: A cross-sectional study collected sociodemographic, occupational, medical and biometric data from 616 men and women aged 20–60 years who were residents of three communities within the Tierra Blanca region in Mexico. Kidney function was assessed by standardized serum creatinine and estimated glomerular filtration rate (eGFR) and semi-quantitative albumin-to-creatinine ratio (ACR). To examine the distribution of decreased kidney function within the population, age- and sex-adjusted prevalence of low eGFR (≤60 mL/min/1.73 m 2 ) was estimated for all participants and across occupations. Multivariable logistic regression was used to assess the association of occupation with having low eGFR. Results: Of the 579 participants analysed (37 excluded due to missing data), the age- and sex-adjusted prevalence of low eGFR was 3.5%. Agriculture was the occupation associated with the highest adjusted prevalence of low eGFR (8.8%), with 1 in every 11 agricultural workers having low eGFR. Working in agriculture was independently associated with more than a 5-fold risk of having low eGFR [odds ratio 5.2 (95% confidence interval 1.1–24.3), P = 0.032], after adjustment for age, sex, diabetes, hypertension, body mass index, ACR and family history of KD. Additionally, a quarter of the population (25%) had either low eGFR or an ACR >30 mg/g, mostly due to albuminuria. Conclusions: Our work suggests that there is a high prevalence of decreased kidney function in Tierra Blanca, particularly amongst agricultural workers.